2014
DOI: 10.1186/s40478-014-0141-7
|View full text |Cite
|
Sign up to set email alerts
|

Stereological study of the neuronal number and volume of 38 brain subdivisions of subjects diagnosed with autism reveals significant alterations restricted to the striatum, amygdala and cerebellum

Abstract: IntroductionA total of 38 brain cytoarchitectonic subdivisions, representing subcortical and cortical structures, cerebellum, and brainstem, were examined in 4- to 60-year-old subjects diagnosed with autism and control subjects (a) to detect a global pattern of developmental abnormalities and (b) to establish whether the function of developmentally modified structures matches the behavioral alterations that are diagnostic for autism. The volume of cytoarchitectonic subdivisions, neuronal numerical density, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 118 publications
(159 reference statements)
7
110
3
Order By: Relevance
“…PC loss has been observed in several autopsy studies of autistic patients (Palmen et al, 2004;Whitney et al, 2008;Skefos et al, 2014;Wegiel et al, 2014). Regarding animal models, Lurcher chimeric mice, which show cerebellar abnormalities including postnatal loss of PCs, display behavioral inflexibility and repetitive behavior (Martin et al, 2010).…”
Section: Pcs and Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…PC loss has been observed in several autopsy studies of autistic patients (Palmen et al, 2004;Whitney et al, 2008;Skefos et al, 2014;Wegiel et al, 2014). Regarding animal models, Lurcher chimeric mice, which show cerebellar abnormalities including postnatal loss of PCs, display behavioral inflexibility and repetitive behavior (Martin et al, 2010).…”
Section: Pcs and Autismmentioning
confidence: 99%
“…The cerebellum is involved not only in the control of balance, motor coordination, and learning, but also in higher order emotional, social, and cognitive functions, mainly through its projections (via the thalamus) to various cortical regions including the prefrontal, parietal, and limbic cortex (Fatemi et al, 2012;Reeber et al, 2013;Strick et al, 2009). Notably, Purkinje cell (PC) loss is one of the most common anatomical abnormalities seen in autopsy studies of autistic patients (Palmen et al, 2004;Whitney et al, 2008;Skefos et al, 2014;Wegiel et al, 2014). Cerebellar injury has been associated with a high incidence of ASDs (Wang et al, 2014), and patients with diseases confined to the cerebellum often demonstrate abnormalities seen in ASDs (Schmahmann, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The affected structures are hippocampal region with the CA fields, the dentate gyrus, and the subicular complex and the adjacent perirhinal, entorhinal, and parahippocampal gyrus (45). Studies have shown psychiatric co-morbidities in temporal lobe epilepsy and temporal lobe atrophy in relation to Alzheimer's disease (13,22,36,51,66).…”
Section: █ Discussionmentioning
confidence: 99%
“…Given a resolution of the confocal microscope of around 1 µm in axial direction, this density scales to 9 · 10 5 puncta/mm 3 . With a neuron density of 2,485 neurons/mm 3 in the human GPe [Wegiel et al, 2014], we get 362 puncta/neuron, and thus on average around 3.6 functional gap junctions per neuron. In PD patients, we detected around 1,300 puncta/mm 2 , which relates to roughly 5.2 functional gap junctions per neuron.…”
Section: Estimated Connectivity Within the External Part Of The Globumentioning
confidence: 99%
“…Given a network of 300 GPe neurons, a connection probability of 1.4 % would be equivalent to on average 2.1 unidirectional synapses per neuron. However, for realistic numbers of neurons -about 45,960 neurons in the rat GP [Oorschot, 1996] or about 904,365 neurons in the human GPe [Wegiel et al, 2014] -we would estimate a much higher number of synapses per neuron. It thus makes more sense to consider the number of inputs that a GPe neuron receives from other neurons.…”
Section: Estimated Connectivity Within the External Part Of The Globumentioning
confidence: 99%